Implementación de Metodologías Cualitativas para la Evaluación Visual de Ríos: Estudio de Caso Río Surba - Duitama - Garavito Cerón, Laura Fernanda; González Vega, Paula Andrea (Universidad Antonio Nariño, 2022)
This research is based on the integrated water resource management developed in the municipality of Duitama, selecting as a case study the Surba River, a river where validated protocols and primers were implemented to visually evaluate the conditions of the riverbed. Six monitoring points were selected along the river to determine water quality and ecological status at each point, taking into account significant changes in vegetation, urbanization, development of agro-industrial activities, and recreational and leisure activities. In addition, physicochemical parameters were evaluated and analyzed both in situ and in the environmental engineering laboratory, to reinforce the study carried out with the protocol and primers. The results obtained showed that the Surba River has an acceptable ecological status and that actions are required to improve the conditions of the riverbed and water quality.